2015
DOI: 10.1002/jcu.22266
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of serous surface papillary borderline ovarian tumor: A case series with a review of the literature

Abstract: Serous surface papillary borderline ovarian tumors (SSPBOTs) are a rare morphologic variant of serous ovarian tumors that are typically confined to the ovarian surface, while the ovaries themselves tend to appear normal in size and shape. In this report, we describe the findings from five premenopausal women diagnosed with SSPBOTs, in whom ultrasound showed grossly normal ovaries that were partially or wholly covered with irregular solid tumors. In all five cases, histologic examination showed evidence of bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 17 publications
(34 reference statements)
1
33
0
Order By: Relevance
“…12,13 The important finding that differentiates SSPBTs from other malignant lesions is the presence of normal ovaries, or at least some normal ovarian tissue, completely or partially surrounded by the solid tumor (Figures 1-3). 9,12,13 Thus, awareness of this disease entity is very important in the diagnosis and determination of appropriate treatment options. 9 Prior knowledge of the tumor type and the presence of normal ovaries, or at least some normal ovarian tissue, is also likely to facilitate attempts to conserve the ovaries during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,13 The important finding that differentiates SSPBTs from other malignant lesions is the presence of normal ovaries, or at least some normal ovarian tissue, completely or partially surrounded by the solid tumor (Figures 1-3). 9,12,13 Thus, awareness of this disease entity is very important in the diagnosis and determination of appropriate treatment options. 9 Prior knowledge of the tumor type and the presence of normal ovaries, or at least some normal ovarian tissue, is also likely to facilitate attempts to conserve the ovaries during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,13 Thus, awareness of this disease entity is very important in the diagnosis and determination of appropriate treatment options. 9 Prior knowledge of the tumor type and the presence of normal ovaries, or at least some normal ovarian tissue, is also likely to facilitate attempts to conserve the ovaries during surgery. 9 There are specific merits associated with each imaging modality in the evaluation of SSPBTs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ludovisi et al reported the ultrasonographic findings that are helpful in diagnosis of serous ovarian tumors and serous surface papillary borderline ovarian tumors. Given these findings, it is possible to perform fertility-sparing surgery in those cases [ 24 ].…”
Section: Discussionmentioning
confidence: 99%